Habitus in The Implementation of Pancasila Student Profile Strengthening Project Through Entrepreneurship Project at School - Hardiyanto, Fendy Dwi; Atmaja, Hamdan Tri; Arsal, Triwathy (Universitas Negeri Semarang, 2023)
Indonesian education remains a complex challenge. In addition to quality issues, it faces the challenge of the waning character of the younger generation. This study aimed to identify the habitus in implementing Pancasila student profile strengthening project (P5) through a local wisdom-based entrepreneurship project at SMA Negeri 1 Kendal. A qualitative research method was employed in this study. The results showed that the principal, P5 team, assisting teachers, and learners' roles determine the project's success. The learners' habitus also plays an essential role in their success in completing the project. The research novelty lies in Pierre Bourdieu's utilization of the habitus concept to analyze entrepreneurship project implementation. Systematically designed project implementation activities to strengthen the Pancasila learner profile can serve as a medium for developing students with noble character, faith, devotion to God; cooperation; critical thinking; creativity; resilience, and independence. The entrepreneurship project is also an internalization of students' exterior and interior habitus. In addition, this study is expected to be beneficial as a reference for schools designing P5 activities. Schools should focus more on the existence and condition of learners' habitus in conceptualizing P5 activities in their respective schools.